POPULATION, ECONOMIC GROWTH AND DEVELOPMENT IN THE EMERGING ECONOMIES - Klaudia Guga; Lorena Alikaj; Fjona Zeneli (European Scientific Journal, ESJ, 2015)
The impact of population on economic development is an issue that has sparked debate across different organizations. Despite discussions, one thing is clear: developing countries are not able to afford a very large increase in population. Unlike developing countries which are facing increasing number of population Albania has recently decrease of population. The main challenge for Albania is: population is ageing; this brings reduction in workforce participation. The methodology consists in using secondary data from World Bank reports for econometric approach, obtaining quantitative results through regression analysis, for a period of 24 years (1990-2014) with the purpose to examine the economic effects of the demographic transition in developing countries. The objective of this paper is to determine main demographic factors that affect economic development and economic growth in developing countries, empirically stated for Albania case. By identifying the factors that influence the economic decrease we have the opportunity to put forward in the future the best policies to ensure sustainable economic growth.